1998
DOI: 10.1152/physiologyonline.1998.13.4.157
|View full text |Cite
|
Sign up to set email alerts
|

Capacitative Calcium Entry

Abstract: Capacitative Ca(2+) entry is a recently discovered Ca(2+) entry pathway that is activated on depletion of intracellular Ca(2+) stores, providing an avenue for store refilling. Despite recent progress in elucidating the capacitative Ca(2+) entry pathway, the mysteries of its molecular identity, its biophysical properties, and the store depletion signal remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 15 publications
3
36
0
1
Order By: Relevance
“…Notice that the capacitative Ca 2ϩ entry (CCE) becomes significantly larger in cells pretreated with ryanodine. The result is consistent with the suggestion that sustained depletion of ER Ca 2ϩ is required for full activation of the CCE pathway (28,29).…”
Section: Stable Expression Of Ryr and Bcl-xl In Cho Cells-supporting
confidence: 92%
“…Notice that the capacitative Ca 2ϩ entry (CCE) becomes significantly larger in cells pretreated with ryanodine. The result is consistent with the suggestion that sustained depletion of ER Ca 2ϩ is required for full activation of the CCE pathway (28,29).…”
Section: Stable Expression Of Ryr and Bcl-xl In Cho Cells-supporting
confidence: 92%
“…These latter data are inconsistent with the involvement of a physical interaction between the ER and the plasma membrane in the activation of SOC. Another model which has received some consideration involves vesicle fusion as a mechanism whereby Ca2+ influx channels are inserted into the plasma membrane upon internal Ca2+ store depletion (Holda et al, 1998). However, Hoth and Penner (1992) had previously reported that there was no change in the capacitance during activation of Ca2+ influx, a finding inconsistent with vesicle fusion.…”
mentioning
confidence: 99%
“…1; for review see Refs. [2][3][4][5][6]. Elevations of [Ca 2ϩ ] i mediate the signal transduction from the plasma membrane agonist receptors to the Ca 2ϩ -sensitive intracellular targets, modulating a variety of cellular functions, including secretion, enzyme activation, gene expression, and proliferation.…”
mentioning
confidence: 99%